Retroperitoneal Extrarenal Angiomyolipomas: An Evidence-Based Approach to a Rare Clinical Entity - Emmanuel J. Minja; Megan Pellerin; Nicole Saviano; Ronald S. Chamberlain (Case Reports in Nephrology)
Extrarenal angiomyolipomas (ERAMLs) are rare tumors that present as incidentalomas upon imaging for other conditions. Retroperitoneal ERAMLs present a unique challenge from a diagnostic and treatment standpoint as they can mimic other benign and malignant retroperitoneal tumors. We present a case of a 39-year-old female with a 19.3 cm × 13.5 cm × 10.7 cm left extrarenal retroperitoneal mass. Histopathologic examination and HMB-45 staining revealed the mass to be a retroperitoneal ERAML. Our case report provides a comprehensive literature review and an evidence-based algorithm for taking care of patients with ERAMLs.